Comparative neuropharmacology of N-(2-methoxybenzyl)-2, 5-dimethoxyphenethylamine (NBOMe) hallucinogens and their 2C counterparts in male rats. (November 2018) - Elmore, Joshua S.; Decker, Ann M.; Sulima, Agnieszka; Rice, Kenner C.; Partilla, John S.; Blough, Bruce E.; Baumann, Michael H.
Abstract: 2, 5-Dimethoxyphenethylamines (2C compounds) are 5-HT2A/2C receptor agonists that induce hallucinogenic effects. N -methoxybenzylation of 2C compounds markedly increases their affinity for 5-HT2A receptors, and two such analogs, 2-(4-chloro-2, 5-dimethoxyphenyl)- N- [(2-methoxyphenyl)methyl]ethanamine (25C-NBOMe) and 2-(4-iodo-2, 5-dimethoxyphenyl)- N- [(2-methoxyphenyl)methyl]ethanamine (25I-NBOMe), have emerged in recreational drug markets. Here, we investigated the neuropharmacology of 25C-NBOMe and 25I-NBOMe in rats, as compared to their 2C analogs and the prototypical 5-HT2A/2C agonist 1-(4-iodo-2, 5-dimethoxyphenyl)propan-2-amine (DOI). Compounds were tested in vitro using 5-HT2A receptor binding and calcium mobilization assays. For in vivo experiments, 25C-NBOMe (0.01–0.3 mg/kg), 25I-NBOMe (0.01–0.3 mg/kg), 2-(4-chloro-2, 5-dimethoxyphenyl)ethanamine (2C-C) (0.1–3.0 mg/kg), 2-(4-iodo-2, 5-dimethoxyphenyl)ethanamine (2C-I) (0.1–3.0 mg/kg) and DOI (0.03–1.0 mg/kg) were administered subcutaneously (sc) to male rats, and 5-HT2A -mediated behaviors were assessed. NBOMes displayed higher affinity for 5-HT2A receptors than their 2C counterparts but were substantially weaker in functional assays. 25C-NBOMe and 25I-NBOMe were much more potent at inducing wet dog shakes (WDS) and back muscle contractions (BMC) when compared to 2C-C and 2C-I. Pretreatment with the selective 5-HT2A antagonist (R)-(2, 3-dimethoxyphenyl)1-[2-(4-fluorophenyl)ethyl]-4-piperidinylmethanol (M100907) reversed behaviors produced by all agonists. Interestingly, binding affinities at the 5-HT2A receptor were significantly correlated with potencies to induce BMC but not WDS. Our findings show that NBOMes are highly potent 5-HT2A agonists in rats, similar to effects in mice, and consistent with the reported hallucinogenic effects in human users. This article is part of the Special Issue entitled 'Psychedelics: New Doors, Altered Perceptions'. Graphical abstract: Highlights: 25C-NBOMe and 25I-NBOMe are 30-fold more potent at rat 5-HT2A receptors when compared to 2C-C and 2C-I. NBOMe compounds are more potent than 2-C compounds at inducing wet dog shakes (WDS) and back muscle contractions (BMC). WDS and BMC produced by NBOMe are reversed by the 5-HT2A antagonist M100907. NBOMe compounds are ultrapotent 5-HT2A agonists in rats, consistent with their powerful hallucinogenic effects in humans.